What happened to Nina? : [large type] a thriller - McTiernan, Dervla (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Nina and Simon are the perfect couple. Young, fun and deeply in love. Until they leave for a weekend at his family's cabin in Vermont, and only Simon comes home. What happened to Nina? Nobody knows. Simon's explanation about what happened in their last hours together doesn't add up. Nina's parents push the police for answers, and Simon's parents rush to protect him. They hire expensive lawyers and a PR firm that quickly ramps up a vicious, nothing-is-off-limits media campaign. How far will his family go to keep him safe? Soon, facts are lost in a swirl of accusation and counter-accusation. Everyone chooses a side, and the story goes viral, fuelled by armchair investigators and wild conspiracy theories and illustrated with pretty pictures taken from Nina's social media accounts. Journalists descend on their small Vermont town, followed by a few obsessive "fans. How far will her family go to get the truth? Nina's family is under siege, but they never lose sight of the only thing that really matters -- finding their daughter. Out-gunned by Simon's wealthy, powerful family, Nina's parents recognize that if playing by the rules won't get them anywhere, it's time to break them.